Entre étalement et densification : une approche fine de l’urbanisation littorale sur la Côte bleue, Provence - Samuel Robert (Cybergeo, 2016)
To assist spatial planning and environmental management policies in coastal areas, the monitoring of urban sprawl and the characterization of the evolution of built-up areas are essential prerequisites. In this perspective, the production of land use data sets on a large-scale is necessary and many governmental and research initiatives have been engaged for this purpose. Taking as a case study the coastal zone of the Côte bleue, in Provence, this paper reports on an experiment of land use mapping on a large-scale, based on a classification made of 44 urban classes compliant with Corine Land Cover. Available with four versions (1998, 2003, 2008 and 2011), the resulting database allows an accurate characterization of the recent evolution of the urbanization. Urban sprawl and urban densification can be studied using spatial analysis. Thus, the transformation of artificial areas appears much higher than urban sprawl. However, urban areas composed of single houses still prevail.